Dakwah Dan Transformasi Keberagamaan Urban: Kajian Komunikasi Urban Sufisme Dan Urban Salafi - Noor Aziziah Bt. Adam; Darussalam Syamsuddin; Wawan Wilano (Jurnal Ilmu Agama Indonesia, 2026)
The development of urban society has introduced new complexities in religious life, driven by technological advancement, social diversity, and changing patterns of religious communication. This situation requires da‘wah to move beyond traditional approaches and to develop contextual and adaptive communication models. This article aims to examine the role of da‘wah as a medium of communication in mediating transformations of urban religiosity through the phenomena of Urban Sufism and Urban Salafism. This study employs a qualitative approach with a descriptive-analytical design. Data were collected through a literature review of works on da‘wah and Islamic communication, classical Islamic texts (kitab), and an examination of da‘wah practices and materials circulating in urban public spaces, including digital media platforms. Data analysis was conducted using discourse analysis and da‘wah communication approaches to reveal patterns of message delivery, communication strategies, and the construction of religious meaning produced by these two da‘wah models. The findings indicate that da‘wah plays a significant role in shaping the transformation of urban religiosity, particularly in terms of religious awareness, Islamic identity, and religious practices. Urban Sufism presents a spiritual-communicative model of da‘wah that emphasizes inner experience, empathetic engagement, and dialogue with modernity, while Urban Salafism represents a normative-textual model that prioritizes doctrinal certainty and the reinforcement of religious identity. These two approaches demonstrate dynamic interactions and contestations of religious discourse within urban public spaces through narratives, symbols, and da‘wah communication strategies. This study underscores that da‘wah in urban society functions strategically as a medium of communication that shapes and continuously transforms patterns of religiosity in a dynamic and sustainable manner.